!!SOS!!Mg ---> MgO ---> MgCl ---> Mg(OH)2 ---> MgSO4Осуществить цепочку превращ

0
0

!!SOS!!Mg —> MgO —> MgCl —> Mg(OH)2 —> MgSO4Осуществить цепочку превращений!!​

0
0

Ответ:

Объяснение:

2Mg + O₂ = 2MgO

MgO + 2HCl = MgCl₂ + H₂O

MgCl₂ + 2NaOH = Mg(OH)₂ + 2NaCl

Mg(OH)₂ + H₂SO₄ = MgSO₄ + 2H₂O

0
0

1)  \: 2Mg + O_{2} = 2MgO \\ </p><p>2)  \: MgO + 2HCl = MgCl_{2} + H_{2}O \\ </p><p>3)  \: MgCl_{2} + 2NaOH = Mg(OH)_{2} + 2NaCl \\ </p><p>4)  \: Mg(OH)_{2} + H_{2}SO_{4} = MgSO_{4} + 2H_{2}O

Показано 2 результата